Koleksi hadis-hadis hukum - T.M. Hasbi Ash-Shiddieqy (Pustaka Rizki Putra, 2001)
tr, jil. 2=c.1; jil.4=c.1; jil. 6=c.1/Oen, Jil. 3=c.1/oen, jil.1=c.1/oen, jil.5=c.1/ir,jil.1,c.2 ; jil.8,c.1/tr, jil.9=c.1/stc13,jil6,c.1